Anterior mitral valve aneurysm: a rare sequelae of aortic valve endocarditis. Issue 1 (March 2016) - Janardhanan, Rajesh; Kamal, Muhammad Umar; Riaz, Irbaz Bin; Smith, M Cristy
Summary: In intravenous drug abusers, infective endocarditis usually involves right-sided valves, with Staphylococcus aureus being the most common etiologic agent. We present a patient who is an intravenous drug abuser with left-sided (aortic valve) endocarditis caused by Enterococcus faecalis who subsequently developed an anterior mitral valve aneurysm, which is an exceedingly rare complication. A systematic literature search was conducted which identified only five reported cases in the literature of mitral valve aneurysmal rupture in the setting of E. faecalis endocarditis. Real-time 3D-transesophageal echocardiography was critical in making an accurate diagnosis leading to timely intervention. Learning objectives Early recognition of a mitral valve aneurysm (MVA) is important because it may rupture and produce catastrophic mitral regurgitation (MR) in an already seriously ill patient requiring emergency surgery, or it may be overlooked at the time of aortic valve replacement (AVR). Real-time 3D-transesophageal echocardiography (RT-3DTEE) is much more advanced and accurate than transthoracic echocardiography for the diagnosis and management of MVA.